MULTICULTURALISM AND HOTEL NARRATIVE: A HARMONIOUS BLEND OF DIVERSITY AT HOTEL SHAHJAHAN IN SANKAR’S CHOWRINGHEE - Suchismita Panda, Prof. (Dr) Indrani Singh Rai (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The ‘Hotel Shahjahan’, one of the largest hotels in Calcutta is the most significant landmark in Sankar’s classic creation Chowringhee, bringing together various cultures, traditions, rituals, essences, and lifestyles under an umbrella. The novel is a colourful collage of various plots revolving around characters from different countries, communities, and colours. It witnesses the live celluloid of multiple and multicultural individuals. Post-independent Indian society could not easily get rid of the British cultural influence, though it could not have been possible. Being the capital of India for almost half of a century during the British regime, Calcutta turned into the cultural capital of the country. Mani Shankar Mukherjee epitomizes this melting pot of multiculture in his legendary creation Chowringhee. The blend of different languages, cuisines, and customs creates a unique ambiance that celebrates diversity and fosters understanding among communities. Marco Polo from far Greece, British citizen Susan Munro and musician P.C. Gomez, Rosie from the farthest corner of Africa, an elderly American lady Dr Sutherland or Byron, Jimmy, Mr. Claybar encountered Sata Bose, Mr. Madhav Pakrashi, Mr. Agrawal, Mr. Chatterjee, Kaberi Guha and many characters of typical Indians communities. This article is an attempt to investigate and analyze the characters from several cultures in the novel highlighting the fragments of their lives associated with the ‘Hotel Shahjahan’.